Do investment strategies based on previous performance yield higher returns? Evidence from South African bond funds - Myoli, Monwabisi Joseph (Graduate School of Business (GSB), 2020)
This paper examines the performance and performance persistence of South African bond mutual funds. To my knowledge, this paper is among the first research papers to focus on South African bond mutual funds. I utilize the Sharpe Ratio, the modified Sharpe ratio, Jensen's alpha and the multi-index models to examine whether peformance is influenced by the performance measure used. In addition, I examine the impact of conditioning information variables on performance by further measuring performance using the conditional single-index and conditional multi-index models. To test for persistence, I use the contigency tables and crosssectional regressions. I find empirical evidence to suggest that South African bond funds are not able to outperform the market. These findings are consistent across the Sharpe ratio, the unconditional single-index alphas and the unconditional multi-index alphas. When I consider the modified and conditional versions of these models, I conclude that the modified Sharpe ratio improves fund performance when compared to the original Sharpe ratio. Additionally, I conclude that incorporating conditional information variables does not offer significant improvements on the results. However, despite the observed underperformance, I note the improvement on alphas when these conditioning variables are considered. In examining performance persistence, I find evidence to suggest that, in the short-term, persistence is not sensitive to the persistence methodology used. However, I observe that persistence is rather sensitive to the performance model used. Over the longer-term, I find evidence to conclude that persistence is greatly sensitive to both the performance model used as well as the methodology used to test such persistence. My results suggest that the South African bond market is efficient and thereby in support of a passive management investment strategy. Nonetheless, my results urge for a need for bond funds to pay special attention to their trading costs in order to maximise returns for their investmens